Association of accelerometer-measured sleep duration and different intensities of physical activity with incident type 2 diabetes in a population-based cohort study - Xinyi Jin; Yilin Chen; Hongliang Feng; Mingqing Zhou; Joey W.Y. Chan; Yaping Liu; Alice Pik Shan Kong; Xiao Tan; Yun-Kwok Wing; Yannis Yan Liang; Jihui Zhang (Elsevier, 2024)
Purpose: The aim of the current study was to investigate the association of accelerometer-measured sleep duration and different intensities of physical activity (PA) with the risk of incident type 2 diabetes in a population-based prospective cohort study. Methods: Altogether, 88,000 participants (mean age = 62.2 ± 7.9 years, mean ± SD) were included from the UK Biobank. Sleep duration (short: <6 h/day; normal: 6-8 h/day; long: >8 h/day) and PA of different intensities were measured using a wrist-worn accelerometer over a 7-day period between 2013 and 2015. PA was classified according to the median or World Health Organization-recommendation: total volume of PA (high, low), moderate-to-vigorous PA (MVPA) (recommended, not recommended), and light-intensity PA (high, low). Incidence of type 2 diabetes was ascertained using hospital records or death registries. Results: During a median follow-up of 7.0 years, 1615 incident type 2 diabetes cases were documented. Compared with normal sleep duration, short (hazard ratio (HR) = 1.21, 95% confidence interval (95%CI): 1.03-1.41) but not long sleep duration (HR = 1.01, 95%CI: 0.89-1.15) was associated with excessive type 2 diabetes risk. This increased risk among short sleepers seems to be protected against by PA. Compared with normal sleepers with high or recommended PA, short sleepers with low volume of PA (HR = 1.81, 95%CI: 1.46-2.25), not recommended (below the World Health Organization-recommended level of) MVPA (HR = 1.92, 95%CI: 1.55-2.36), or low light-intensity PA (HR = 1.49, 95%CI: 1.13-1.90) had a higher risk of type 2 diabetes, while short sleepers with a high volume of PA (HR = 1.14, 95%CI: 0.88-1.49), recommended MVPA (HR = 1.02, 95%CI: 0.71-1.48), or high light-intensity PA (HR = 1.14, 95%CI: 0.92-1.41) did not. Conclusion: Accelerometer-measured short but not long sleep duration was associated with a higher risk of incident type 2 diabetes. A higher level of PA, regardless of intensity, potentially ameliorates this excessive risk.